1991
DOI: 10.2466/pr0.1991.69.2.579
|View full text |Cite
|
Sign up to set email alerts
|

Group Effects on Decision-Making by Burglars

Abstract: 30 active burglars were observed and interviewed extensively over a period of 16 months. They were asked to evaluate sites they had previously burglarized and those burglarized by others, as to their perceived vulnerability to burglary. Burglars who evaluated sites singly rated the sites more vulnerable than those same burglars when evaluating the sites in the presence of their usual co-offenders—showing a trend toward more cautious decision-making while in groups—a group polarization effect. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It is, to use Black's (1983) elegant phrase, "crime as social control." Extant studies are largely descriptive and examine reprisal tangentially to other dynamics relevant to offender groups and settings (see, e.g., Cromwell et al 1991;Decker and Van Winkle 1996;Jacobs 2000;Luckenbill 1977;Meier, Kennedy, and Sacco 2001). These studies do not explore retaliation's essential variation, nor do they attempt to organize it in any systematic way.…”
Section: The Retaliation Literaturementioning
confidence: 99%
“…It is, to use Black's (1983) elegant phrase, "crime as social control." Extant studies are largely descriptive and examine reprisal tangentially to other dynamics relevant to offender groups and settings (see, e.g., Cromwell et al 1991;Decker and Van Winkle 1996;Jacobs 2000;Luckenbill 1977;Meier, Kennedy, and Sacco 2001). These studies do not explore retaliation's essential variation, nor do they attempt to organize it in any systematic way.…”
Section: The Retaliation Literaturementioning
confidence: 99%
“…Those who self-select for any situation are likely attuned to its permitted behaviors and requirements, and they often reinforce one another in the direction of their common inclinations. One study found that burglars report engaging in more burglary when together in groups (Cromwell, Marks, Olson, & Avary, 1991). In the case of the SPE, if the individuals who volunteered possessed traits associated with abusiveness, they could well have reinforced one another in that direction.…”
mentioning
confidence: 99%
“…Similar findings have been reported by other researchers such as Leibrich (1993, pp.56–7) and Cromwell et al . (1991, p.83), who have all identified the importance of a ‘decision’ to give up crime. Shover (1983:) suggests a change in goals, and tiredness of a criminal lifestyle, can all cause individual reflection, contributing to a desire to change and move away from criminal behaviour.…”
Section: Context and Literaturementioning
confidence: 99%